Qualidade microbiológica de ostras (Crassostre sp.) e de águas coletadas em cultivos e em bancos naturais da Ilha de São Luís, MA - Sousa, Claudio Baltazar de (2021)
The high consumption of bivalve mollusks in natura in coastal areas enables the occurrence of diseases transmitted by these foods, especially when the health of the fish produced is related to anthropogenic impacts on the estuaries. Thus, the present research aimed to evaluate the microbiological quality of oysters and water both in natural beds and in oyster farms located on the Island of São Luís, MA. For this purpose, 60 samples were analyzed from September 2020 to February 2021, 30 of water and 30 of oysters (Crassostrea sp.) collected directly from shellfish farmers and farm owners in the municipalities of the Island of São Luís, MA. For the determination of total coliforms and E. coli in the water samples, the technique recommended by APHA (2012) was used using the Colilert® rapid method. For the enumeration of total and thermotolerant coliforms in oysters were performed by the Most Probable Number (MPN) method and E. coli by the technique described by Vanderzant and Splittstoesser (1992). Enumeration of coagulase positive Staphylococcus in oysters was performed according to (SILVA et al., 2017). Salmonella sp., Aeromonas sp. and Vibrio sp. enumeration in oysters were performed according to the methodologies recommended by APHA (2012), (CARNARHAN et al.,1991) and Bacteriological Analytical Manual online (ELLIOT, KAYSNER; TAMPLIN, 2004). The results in geometric mean count of E. coli in the water samples ranged from 604.29 to 1130.79 NMP/100ml demonstrating unsatisfactory microbiological quality. For the oysters, 8 (26.66%) of the 30 samples were unsuitable for consumption, 4 samples (13.33%) due to the presence of Salmonella sp. and 4 samples (13.33%) due to E. coli counts above the limits of the legislation. Thus, it is recommended the implementation of good handling practices, use of the purification technique and monitoring of water quality throughout the mollusk production chain.